The Influence Of Work Life Balance And Work Environment On Employee Job Satisfaction Of PT. Sucofindo Makassar Branch - Amin, Muhammad Ridwan; Kiki Sudiana (Jurnal Ekonomi, 2024)
PT Sucofindo Makassar branch is one of the state-owned companies tasked with encouraging the development of the national industry and supporting various sectors in meeting applicable standards and regulations. The problem that occurs is the increase in employee turnover and the level of employee absenteeism that has not reached perfect numbers. Good job satisfaction can be supported by work-life balance and a good work environment. There are many factors that can affect employee performance results, namely the lack of satisfaction provided by the company. The purpose of this research is to determine the conditions of Work-Life Balance, Work Environment, and Job Satisfaction of Employees as well as to understand the influence of Work-Life Balance and Work Environment on Employee Job Satisfaction at PT Sucofindo Makassar Branch. This research was conducted using a descriptive causal technique with a quantitative approach. The population studied consisted of employees of PT Sucofindo Makassar branch. A sample of 97 employees was selected using probability sampling with simple random sampling. Data was collected through questionnaires distributed to all employees of PT Sucofindo Makassar branch. The data was processed using a quantitative approach through descriptive analysis, classical assumption tests, and multiple linear regression analysis. Based on the calculations of descriptive statistical analysis, the results show that respondents rated the work-life balance, work environment, and job satisfaction in the "very high" category. Hypothesis testing indicated that work-life balance has a positive and significant effect on employee job satisfaction. The work environment also has a positive and significant effect on employee job satisfaction. Furthermore, work-life balance and the work environment together have a positive and significant impact on employee job satisfaction with a value of 57%.